The effect of quality of presentation of financial statements and accessibility of financial statements on financial management accountability: case studies in regional apparatus organizations in the City of Bandung in 2023 - Simanjorang, Mega; Rachman, Andry Arifian (Gema Wiralodra, 2023)
This study aims to examine the effect of the quality of presentation of financial reports and the accessibility of financial reports on the accountability of financial management in Bandung City Regional Apparatus Organizations. This research is quantitative. The data used were primarily questionnaires distributed to 54 respondents, namely the Heads of Regional Apparatus Organizations and Finance Sub-Sections of each agency and service office. The sampling technique used was the purposive sampling method—data collection techniques used in this study using survey methods. The analytical method used is multiple linear regression analysis with the SPSS application tool. This study uses traditional assumptions, namely the normality test, heteroscedasticity test, autocorrelation test, multicollinearity test, and hypothesis testing using the t-test and F-test. The results show that the quality of the presentation of financial statements and the accessibility of financial reports have a simultaneous influence on financial management accountability. The quality of presentation of financial statements partially has a significant positive direction, and the accessibility of financial reports has a significant positive effect on financial management accountability.